The Black Sea as Mare clausum: Turkey's special role in the regional security architecture - Daria Isachenko; Göran Swistek (Stiftung Wissenschaft und Politik (SWP), 2023)
The Black Sea is a region of tension. It is the arena of the Russia-NATO confrontation while at the same time serving as a projection area for Russian and Turkish visions of regional order. Turkey's special role in the region stems primarily from the implementation of the Montreux Convention, which for much of the last century has meant a reduction in unilateral spheres of influence and dominance. The non-riparian states are supposed to be excluded. For Turkey, the Montreux Convention is a lever of power. Russia's invasion of Ukraine in February 2022 has enabled it to use this lever even more in the service of its own interests. NATO's room for manoeuvre, on the other hand, has been reduced in the current situation. Turkey is an essential element in the Alliance's collective defence. However, since the outbreak of the Russian war against Ukraine, NATO is no longer present in the Black Sea. This means that an important pillar of deterrence and defence is missing. In this respect, there is a dualism regarding the conceptions of order in the Black Sea region at two different levels: the regional and the global.
Keywords: 320; Black Sea; Black Sea Region; Turkey; Russia; Ukraine; Bosporus; Dardanelles; Sea of Marmara; Sea of Azov; Montreux Convention; Active Endeavour; Black Sea Harmony; BlackSeaFor; Tailored Forward Presence; deterrence and dialogue